Breaking the development logjam : new strategies for building community support - Porter, Douglas R. (ULI-the Urban Land Institute, 2006)
This book explains in plain terms how developers and planners can involve the community in the development process using the latest community engagement tools. It describes why, in these days of more complex projects and development approval procedures, it pays to win citizen support rather than fight opposition.